The Art of Ceramic Extrusion - Händle, Frank; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is ideal for practitioners and managers with low experience in the field. It introduces the theme of extrusion in ceramics and provides checklists, questionnaires, as well as the related literature and websites covering the topic. This Brief is written in a simple language and covers topics such as honeycombs, ceramic filters, auger geometry, wear and tear.
Introduction -- What is extrusion in ceramics? -- Where do we use extrusion in ceramics? The ideal extruder -- Plasticity in ceramics -- Exercises.
Keywords: Manufactures; Ceramic materials; Machines, Tools, Processes; Ceramics